Should Kiribati continue to aim for 100% voluntary non-remunerated blood donation as recommended by the WHO? - Tauma, G. (Public Health Action, 2016)
Setting: Tungaru Central Hospital Blood Bank Laboratory, Nawerewere, Tarawa, Kiribati. Objective: To determine characteristics, deferrals and reasons for deferral amongst blood donors from 2011 to 2016. Design: A cross-sectional study using routinely collected data. Results: From January 2011 to March 2016, 8531 potential blood donors were registered. For each full year, the proportion of voluntary non-remunerated blood donors (VNRBD) was below 10%, although it increased to 13% in 2015. The overall proportion of blood donors deferred increased each year over the 5-year period, from 44% to 57%, with similar increases in deferrals in VNRBD and family replacement donors (FRD). Among all blood donors, a higher proportion of females than males (59% vs. 43%) and VNRBD than FRD (56% vs. 44%) were deferred (P < 0.001). Deferrals were due to 1) failing the medical questionnaire (53%), 2) having anaemia and/or high white cell count (26%), or 3) transfusion-transmissible infections (21%). More VNRBD were deferred due to failing the medical questionnaire, while more FRD were deferred due to anaemia and/or high white-cell count; the number of deferrals was similar for transfusion-transmissible infections. Conclusion: This 5-year study showed that the proportion of VNRBD is low and deferrals are higher for this group than for FRD. There is a strong case for encouraging both types of donor in the country.